The Effectiveness of Game-Based Learning Interactive E-Modules in Enhancing Students' Learning Concentration: A Systematic Literature Review - Arcita Rizara; Dwi Kusumawardani; Mita Septiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This systematic literature review examines the effectiveness of game-based learning (GBL) interactive e-modules in improving students' learning concentration. The study synthesizes the findings from eight research articles published between 2012 and 2025. The analysis reveals that GBL-based e-modules significantly enhance learning motivation, with validity rates ranging from 90% to 99%. Additionally, the use of interactive platforms such as Wordwall, Gimkit, and other digital tools effectively supports various learning styles, particularly visual and kinesthetic learners. The review highlights that student engagement levels improve significantly, ranging from 67.42% to 87.12%. Furthermore, these e-modules positively impact learning outcomes, providing a more engaging and interactive approach to education. By integrating gamification elements, the e-modules create a dynamic and motivating learning environment that fosters better concentration and focus among students. The review concludes that GBL-based e-modules are an effective educational strategy, particularly in geography education at the high school level. These tools not only engage students in a fun and interactive manner but also improve their ability to focus, leading to enhanced learning experiences. As a result, incorporating GBL-based e-modules in educational practices can contribute to better learning concentration and overall academic performance.